Production of Melanin from Bacillus Species Isolated from Rhizosphere Soil (International Journal of Scientific Research in Science and Technology, 2024)
Melanin is an UV protective pigment which has shown its presence all across the living organisms except for viruses, for various functions such as UV-protection, Anti-microbial activity, free radical scavenging activity etc. The pigment is produced in specialized cells called the Melanocytes by the process of Melanogenesis in humans, while it is produced in cytoplasm in bacteria and other prokaryotes. The main enzyme that is responsible for catalyzing the production of melanin from L-tyrosine is ‘Tyrosinase’. It is this enzyme which enables the bacteria to convert amino acid (L-tyrosine) into melanin. The melanin is a polymer which is made from the L-DOPA, DHI, and DHICA monomers. The current study deals with the production and extraction of melanin from Bacillus species isolated from rhizosphere soil of Neelgiri tree and Sagwan tree. The study further deals with melanin and its characterization using UV- visible spectroscopy, FT-IR spectroscopy and its solubility test in different solvents. Undertaking the industrial applications of bacterial melanin, the current study also deals with the UV-protection activity of the extracted melanin, and the antibacterial activity of the melanin extracted from the bacterial isolated.